2006
DOI: 10.1111/j.1365-2141.2005.05904.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immunoglobulin VH genes suggests cutaneous marginal zone B‐cell lymphomas recognise similar antigens

Abstract: Summary Extranodal marginal zone B‐cell lymphomas (EMZL) are thought to develop from reactive infiltrates that represent immune responses to external or auto‐antigens. Except for gastric EMZL, the antigenic triggers of EMZL development are mostly unknown, although a subset of cutaneous EMZL have been associated with Borrelia burgdorferi infections. To further evaluate whether a common antigen may be promoting the development of cutaneous EMZL, the immunoglobulin heavy chain variable (VH) genes from eight USA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…Our results also show that t(11;18)(q21;q21)-positive gastrointestinal MALT lymphomas predominantly rearrange VH3 family and to a lesser extent VH4 and VH1 family genes, in cases 4, 2 and 1 respectively. This is similar to what was previously observed in several studies on MALT lymphoma [27,30,[32][33][34][35]39] and one study on nodal marginal zone lymphoma [28] . In addition, it was found that the two t(11;18)(q21;q21)-negative gastric MALT lymphomas rearranged VH3 and VH1 family genes respectively (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results also show that t(11;18)(q21;q21)-positive gastrointestinal MALT lymphomas predominantly rearrange VH3 family and to a lesser extent VH4 and VH1 family genes, in cases 4, 2 and 1 respectively. This is similar to what was previously observed in several studies on MALT lymphoma [27,30,[32][33][34][35]39] and one study on nodal marginal zone lymphoma [28] . In addition, it was found that the two t(11;18)(q21;q21)-negative gastric MALT lymphomas rearranged VH3 and VH1 family genes respectively (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…gastrointestinal MALT lymphomas is consistent with that reported in similar studies on both gastric and non-gastric MALT lymphomas in which data on the presence of t(11;18)(q21;q21) was not available [26,27,30,[32][33][34][35][36][38][39][40] . In addition, analysis of the VH mutation status in 2 t(11;18)(q21;q21)-negative MALT lymphomas (data not shown) revealed a mutation frequency of 0% and 4.5% respectively, indicating that, similar to what is observed in t(11;18)(q21;q21)-positive MALT lymphomas, t(11;18)(q21;q21)-negative MALT lymphomas can be derived from both naïve and memory B cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Rather, family-specific primers are used so that, for example, 6 or 7 IGH@ V primers are used instead of ~45 individual V primers. However, several lymphomas have been demonstrated to have a nonrandom utilization of gene segments, so rational design of primer sets can optimize detection rates [29, 30]. …”
Section: Antigen Receptor Gene Rearrangementsmentioning
confidence: 99%
“…The finding of continuing accumulation of somatic mutations in Letter to the Editor 249 the clone may indicate that PCMZL is derived not from marginal zone B-cells, but from germinal center B-cells. However, some cases of MALT-type lymphoma showed intraclonal diversity in their V genes and MALT-type lymphoma is hypothesized to be derived from marginal zone B-cells, which are thought to be post germinal memory B-cells [9,10]. In these cases, it has been suggested that the neoplastic clones are probably derived from marginal zone-lymphocytes affected by a germinal center B-cell reaction [10].…”
mentioning
confidence: 99%